Development of DNA barcodes to identify edible mushrooms - Avin, F.A.; Vikineswary, S.; Yee Shin, T.; Bhassu, S. (2012)
Basidiomycetes as one of the largest groups of edible mushrooms have become more important in recent times for their medicinal and nutritional properties. For many years, species of this family have been mainly classified by their common phenotypic traits, however, taxonomic identification based solely on morphological features can be misleading and unreliable. In contrast, DNA based identification provides a powerful and reliable method for taxonomic discrimination of fungi, it can be performed at any growth stages using parts of the fruit body, monoand dikaryotic mycelia, or any other organic fungal. In the current study, three different DNA and c‐DNA molecular markers including Internal Transcribed Spacer (ITS) I and II, Intergenic Spacer (IGS) I, and mitochondrial COXI gene were developed to identify mushroom species and individuals. Phylogenetic trees could clearly distinguish the species of Basidiomycetes by showing distinct clades. Species differentiations were re‐confirmed by AMOVA analysis, nucleotide divergence, haplotyping and P values. Moreover, the designed primers were perfectly matched with the used species, can be employed in phylogenetic studies of other Basidiomycetes. Polymorphism occurred throughout the regions of interest due to insertion‐deletion and point mutations, and can be clearly differentiated within the families as well as genera. This study proved that the three developed molecular markers can be used as the consensus DNA and/or c‐DNA barcodes for taxonomic identification of Basidiomycetes.